(untitled) - Ingham, Barbara (Harlow, England, 2004)
This introductory, concise and non-technical approach to international economics deals with issues in the international environment which are of relevance to UK/European students, relating international economics to the European experience wherever it is appropriate to do so. The book is aimed at undergraduate students taking a course in international economics. As well as students specialising in economics, the book will be useful to students on business studies, management and social science programmes
Keywords: International economic relations,International trade; Case studies,Case studies